Regular feedback to individual endoscopists is associated with improved adenoma detection rate and other key performance indicators for colonoscopy. Issue 6 (6th May 2022) - Lim, Samuel; Tritto, Giovanni; Zeki, Sebastian; DeMartino, Sabina
Abstract : Objective: Monitoring of key performance indicators (KPIs) is a vital element of endoscopy quality improvement. Adenoma detection rate (ADR) is considered the best marker for colonoscopic quality as it inversely correlates with subsequent colonic cancer incidence and mortality, while polyp detection rate (PDR) is an easier-to-calculate surrogate for ADR. This study assessed whether regular feedback to individual endoscopists about their KPIs improved departmental performance. Methods: Individual KPIs were calculated for a period of 8 years (January 2012–December 2019) and fed back to all endoscopists at 6 monthly intervals, alongside anonymised indicators for other endoscopists, aggregate departmental performance data and benchmarks. An automated natural language processing software (EndoMineR) was used to identify adenomas in pathology reports and calculate ADR. Linear regressions were calculated for departmental ADR, PDR and other KPIs at 6 monthly intervals. Results: 39 359 colonoscopies (average 2460 in every 6-month period, range 1799–3059) were performed by an average of 42 (range 34–50) endoscopists. A continuous improvement in collective performance including ADR (12.7%–21.0%, R 2 0.92, p<0.001) and PDR (19.0%–29.6%, R 2 0.77, p<0.001) was observed throughout the study. Other KPIs showed similar improvement. The detection of non-neoplastic polyps did not increase. When analysed separately, ADR and PDR appeared to improve for gastroenterologists and nurse endoscopists but not for surgeons. Conclusion: Regular feedback with individual and departmental KPIs was associated with improved ADR and overall performance throughout the 8-year study period. Concomitant monitoring of ADR and PDR may prevent 'gaming' behaviour and ensure that genuine improvement is achieved.